A biotheology of God’s divine action in the present global ecological precipice - Lisanne D. Winslow (HTS Teologiese Studies/Theological Studies, 2022)
Theological discourse surrounding the environmental crisis has rightly brought to the forefront human agency as a primary causal determinant. However, this article explores a theistic divine action position toward an account of the present global precipice that the earth and all its creatures teeter upon. The first section offers a preferred view of divine action theory, Divine Compositionalism, with explanatory power to account for an ever-changing planet. Furthermore, Divine Compositionalism is used to ground the role of God as Creator and sustainer of all things toward a constructive biotheology. The second section accounts for both human culpability and God’s divine action, retaining human free will and God’s sovereignty within a creation God owns and loves. The final section explores a possible remedy to the environmental precipice through the very elements of human cooperation that ensured the success of our prehistoric ancestors. A cooperative biotheology entails humanity re-claiming its inter-relation with all creatures in a world family while exercising the free will to partner with one another on a spiritual level in accomplishing God’s good and wonderful eternal ideas for the next step in human spiritual development toward earth’s physical evolution.